Hw8-sol - Modern Analysis Homework 8 Possible solutions All problems are worth 5 points 1[12 Rudin Ch 5 problem 1 Solution Since | f x f y | ≤ x

Info iconThis preview shows pages 1–2. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Modern Analysis, Homework 8 Possible solutions All problems are worth 5 points. 1. [12] Rudin, Ch 5, problem 1. Solution: Since | f ( x )- f ( y ) | ≤ ( x- y ) 2 for all x,y ∈ R , if x 6 = y , we have ≤ f ( x )- f ( y ) x- y ≤ | x- y | Letting y → x , of course | x- y | → 0 and 0 → 0, so by the squeeze theorem, we get that lim x → y f ( x )- f ( y ) x- y = 0, ie f ( x ) = 0 for all x ∈ R . By the mean value theorem, this implies that f itself is constant. 2. [18] Rudin, Ch 5, problem 2. Solution: Suppose f ( x ) > 0 in ( a,b ). Notice that f is strictly increasing: given a < x < y < b , by the mean value theorem there exists c ∈ ( x,y ) such that f ( x )- f ( y ) = f ( c )( y- x ). But f ( c ) > 0, so we get that f ( x ) > f ( y ). Let x ∈ ( a,b ). Choose δ > 0 such that [ x- δ,x + δ ] ⊂ ( a,b ). Since [ x- δ,x + δ ] is compact and connected, and since f is continuous, it follows that f ([ x- δ,x + δ ]) = [ c,d ] for some f ( a ) < c,d < f ( b ). Notice actually that c < d since f is strictly increasing. Since f is continuous and one-to-one and [ x- δ,x + δ ] is compact, it follows from Rudin, Theorem 4.17 that g | [ a,b ] 1 is continuous. Now let { y n } be a sequence in ( a,b ) approaching f ( x ) such that y n 6 = f ( x ) for all n ∈ N . Notice that { y n } is eventually in [ c,d ] so we can assume, after possibly taking a subsequence that y n ∈ [ c,d ] \ { f ( x ) } for all n ∈ N . Since g | [ c,d ] is continuous, g ( y n ) converges to some x ∈ [ x- δ,x + δ ]. Notice that we must have x = x since f ( x ) = lim n →∞ f ( g ( y n )) (by continuity of f ), which is just lim n →∞ y n = f ( x ). Since f is strictly increasing, it follows that x = x . Write g ( f ( x ))- g ( y n ) f ( x )- y n = x- g ( y n ) f ( x )- f ( g ( y n )) . Since g ( y n ) → x and f is differentiable at x , this limit exists and equals 1 f ( x ) . Hence g ( f ( x )) = 1 f ( x ) ....
View Full Document

This note was uploaded on 10/18/2011 for the course MATH S4061X taught by Professor Peters during the Spring '11 term at Columbia.

Page1 / 5

Hw8-sol - Modern Analysis Homework 8 Possible solutions All problems are worth 5 points 1[12 Rudin Ch 5 problem 1 Solution Since | f x f y | ≤ x

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online